The use of Earth Observation for wetland inventory, assessment and monitoring - Rebelo, Lisa-Maria; Finlayson, C. Max; Strauch, A.; Rosenqvist, A.; Perennou, C.; Tottrup, C.; Hilarides, L.; Paganini, M.; Wielaard, N.; Siegert, F.; Ballhorn, U.; Navratil, P.; et al. (Ramsar, 2018)
The use of Earth Observation (EO) provides Contracting Parties to the Ramsar Convention on Wetlands with new approaches to ensure the wise use and conservation of wetlands at the national and global levels. EO has many applications including the inventory, assessment and monitoring of wetlands. As technology advances, previous limitations of EO will be reduced, and it is anticipated that the use of EO in the management of wetlands will increase. This Ramsar Technical Report aims to provide practitioners with an overview and illustration, through case studies, on the use of EO for implementation of the Convention and the wise use of wetlands more broadly.